Effect of a parenting and nutrition education programme on development and growth of children using a social safety-net platform in urban Bangladesh: a cluster randomized controlled trialResearch in context - Sheikh Jamal Hossain; Syed Moshfiqur Rahman; Jane Fisher; Anisur Rahman; Fahmida Tofail; Jena Derakhshani Hamadani (Elsevier, 2024)
Summary: Background: Although sustainable development goals mandate for quality early childhood development (ECD) interventions for children <8 years, little occurs for children <3 years, especially in urban settings in low-and-middle-income countries (LMICs). Our primary objective was to measure the effect of an ECD-focused parenting and nutrition education on children's development through home visits using a social safety net platform of urban Bangladesh. Methods: A cluster randomized controlled trial was conducted with mothers of children aged 6-16 months in 20 clusters across the Rangpur city, Bangladesh. The intervention group received fortnightly ECD-focused parenting and nutrition education at homes by local Community Health Workers (CHWs) for one year. Bayley-III was used to measure children's cognitive, language and motor development. Data were analyzed using intention to treat. ClinicalTrials.gov Identifier: NCT03753646. Findings: Out of 599 mother-child dyads, 56.6% mothers were aged ≤ 25 years old. After one year, the intervened children had higher cognitive [Effect size Cohen's d; 0.42 SD (95% CI: 0.58-0.25)], language (0.38 SD, 95% CI: 0.55-0.22) and motor (0.17 SD, 95% CI: 0.01-0.34) development. In the intervention group, mothers experienced less violence [Odds ratio; 0.6 (95% CI: 0.4-1.0)] and fathers engaged more (0.23 SD, CI: 0.39-0.06) in ECD activities with their children compared to the comparison group. Total home stimulation and mothers' knowledge on child care were also improved in the intervention. But the children's growth was not improved. Interpretation: This ECD programme improves the development of children of young mothers in urban settings using a social safety-net platform. The evidence may help in increasing ECD coverage in urban areas in LMICs. Funding: Grand Challenges Canada, Saving Brains Programme Grant Number: SB-1810-20176.